Financial Performance Analysis Using the Economic Value Added (EVA) Method at PT. Indosat Tbk - Roy Seleky; Stenly J. Ferdinandus (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze and determine financial performance using the Economic Value Added method at PT. Indosat Tbk. This study uses secondary data in the form of the financial statements of PT. Indosat Tbk in 2018 – 2021 which is listed on the Indonesia Stock Exchange (IDX). The research method used is analysis with the Economic Value Added (EVA) method. The results of the study stated that the EVA value obtained by PT. Indosat Tbk for four years has a positive value. A positive EVA value indicates that there has been a process of adding economic value to the company because the company has paid its obligations to creditors and shareholders.